MONITORING RESULTS OF GRAY MARMOTH IN A LIMITED SECTION OF ZAILI ALATAU – AREA OF ACTIVE TOURISM IN THE ENVIRONMENT OF ALMATY (Experimental biology, 2022)
The article analyzes the literature and our own (for the period from May 2007 to July 2021) data on the structure of the gray marmot (Marmota baibacina Kastschenko, 1899) settlements on a limited area of the northern slope of the Zailiyskiy Alatau, located near the city of Almaty and often visited by tourists. The northern slope of the Zailiyskiy Alatau is considered a potentially focal area for plague, but it is currently impractical to conduct a survey of the environs of Almaty with the capture of rodents, it is possible to limit ourselves to sanitary and educational work and, if possible, study of dead rodents or their bones. The final results of monitoring marmot settlements on the site confirmed that their spa- tial distribution and fluctuations in numbers depend on a complex of abiotic and biotic factors, and anthropogenic influence is not dominant. If people do not specifically pursue marmots, they get along quite peacefully with a person. The absence of the marmot in the low mountains and the decrease in its number in the subalpine belt of the surveyed area is associated, first of all, with a decrease in livestock grazing, which led to an increase in the height of the grass stand. In the Alpine zone operates of abiotic and biotic factors.